2013
DOI: 10.1111/exd.12083
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus skin colonization is promoted by barrier disruption and leads to local inflammation

Abstract: Experimental mouse models of bacterial skin infections that have been described show that pathogenic microorganisms can readily invade the epidermis and dermis to produce localized infections. We used an epicutaneous mouse skin infection model to determine how the level of barrier disruption by tape-stripping correlates with persistence of Staphylococcus aureus skin colonization, concomitant induction of cutaneous inflammation and infection. Furthermore, we investigated how murine skin responds to S. aureus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 9 publications
3
64
0
4
Order By: Relevance
“…Others have demonstrated that epicutaneous application of S. aureus results in upregulation of proinflammatory cytokines (31). In order to determine whether PSMs play a role in modulating inflammatory gene expression in the skin, we performed RT-PCR on skin sections following exposure to the WT or ⌬psm strain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Others have demonstrated that epicutaneous application of S. aureus results in upregulation of proinflammatory cytokines (31). In order to determine whether PSMs play a role in modulating inflammatory gene expression in the skin, we performed RT-PCR on skin sections following exposure to the WT or ⌬psm strain.…”
Section: Resultsmentioning
confidence: 99%
“…The next day, the stratum corneum barrier was disrupted via mild stripping using three applications of Tegaderm (3M, St. Paul, MN). This technique exposes the keratinocyte layers without creating a wound (31). S. aureus (1 ϫ 10 7 CFU) or PBS was placed with sterile gauze on the stripped skin and occluded with Tegaderm (3M).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…turn leads to microbial invasion by commensal and noncommensal bacteria. This may result in severe SSTIs and can affect wound healing (22,23). This study investigated the efficacy of the lantibiotics nisin, clausin, and the newly described AmyA in the treatment of S. aureus-induced skin infections in mice (24).…”
Section: Fig 3 Representative Photomicrographs Of Sections From Noninmentioning
confidence: 99%
“…Badania przeprowadzone w Stanach Zjednoczonych wykazały, że w 2004 roku spowodował około 1/2 SSTI w Ameryce Północnej i 1/3 w Ameryce Łacińskiej i Europie [17]. Jako przyczynę zwiększo-nej liczby SSTI w przypadku cukrzycy wskazuje się uszkodzenie mechaniczne bariery naskórkowej [18] lub nadmierną kolonizację powierzchni skóry przez bakterie [19]. Kolejnym problemem w przypadku zakażenia skóry gronkowcem złocistym jest upośle-dzona odpowiedź na antybiotykoterapię.…”
Section: Podatność Skóry Na Infekcjeunclassified